This is Improper and Irreligious - Gibson Ncube (African Journal of Gender and Religion (AJGR))
This article examines the negotiation of queer sexuality in Arab-Muslim societies of North Africa. Through close analysis and reading of the film Imarat Yácubyan by Marwan Hamed (Egypt) and the novel Une Mélancolie Arabe by Abdellah Taïa (Morocco), this article examines how media makes it possible to understand how Muslims in North Africa negotiate their sexuality, religion, and practice against backgrounds in which queerness exists in silence and marginality. The selected film and novel demonstrate that Islam is, in fact, a sensuous and queer religion. Designating Islam as queer gestures towards the possibility of imagining non-normative sexualities exiting within and being compatible with the religion. In their different iterations of the intersection of queerness and the practice of Islam, Imarat Yácubyan and Une Mélancolie Arabe open new spaces for understanding Islam and, specifically, what it means to be queer, Arab, and Muslim within the sociocultural context of North African countries.